Integral Assessment of Digital Ecosystem Development in Russian Regions - Korovin, Grigoriy B. (Economy of Regions, 2026)
While digital ecosystems have become a key driver of regional competitiveness and are extensively studied, there remains a lack of comprehensive regional-level assessments of their development. This study presents a methodology for assessing digital ecosystem development across Russian regions by constructing an ecosystem development index and analysing the factors underlying regional differentiation. The methodology is based on statistical analysis and index methods, aggregating normalized indicators across five dimensions: technological foundation, investment and costs, innovation potential, human resource and competency support, and cooperation infrastructure. The analysis relies on official statistical data for 2023. The results reveal pronounced interregional disparities: the gap between leading regions (Nizhny Novgorod Oblqst, Saint Petersburg, Moscow) and lagging regions (Ingushetia, Dagestan, Tuva) reaches up to an order of magnitude. The most advanced digital ecosystems are concentrated in Central and Northwestern Russia, while many regions remain at an early stage of ecosystem formation. The findings may support the development of regional digital transformation strategies and inform policy measures aimed at fostering digital ecosystems. A key limitation of the study is its reliance on the quality and classification of official statistical data, which in some cases required methodological adjustments.